Chiral quizalofop-ethyl and its metabolite quizalofop-acid in soils: Enantioselective degradation, enzymes interaction and toxicity to Eisenia foetida. (June 2016) - Ma, Lin; Liu, Hui; Qu, Han; Xu, Yangguang; Wang, Peng; Sun, Mingjing; Zhou, Zhiqiang; Liu, Donghui
Abstract: An enantioselective chromatographic method to analyze enantiomers of quizalofop-ethyl and its metabolite quizalofop-acid was established using a high-performance liquid chromatography (HPLC) on (R, R) Whelk-O 1 column. The enantioselective degradation kinetics of quizalofop-ethyl and quizalofop-acid in three soils were investigated. Moreover, the interaction with urease and catalase in the soils and the acute toxicity to Eisenia foetida of quizalofop-ethyl were also determined in order to assess their metabolism mechanism and environmental risk. From the results, quizalofop-ethyl was configurationally stable and was hydrolyzed rapidly to quizalofop-acid, which also degraded enantioselectively but slowly, and the inversion of the S-(−)-quizalofop-acid into the R-(+)-quizalofop-acid was observed in Xinxiang soil. In addition, quizalofop-ethyl and quizalofop-acid enantioselectively affected urease activity but not catalase. The acute toxicity assays to earthworm indicated that the racemic quizalofop-ethyl and quizalofop-acid were more toxic than quizalofop-p-ethyl and quizalofop-p-acid respectively, dramatically, the toxicity of the metabolite was much higher than the parent compound. These results revealed the enantioselective degradation of quizalofop-ethyl and quizalofop-acid, and the differences of toxicity among the enantiomers of the parent compound and the metabolite, which should be considered in future environmental risk evaluation. Graphical abstract: Highlights: The degradation of quizalofop-ethyl and quizalofop-acid in the soils was enantioselective. Quizalofop-ethyl and quizalofop-acid enantioselectively affected urease activity but not catalase. Racemic quizalofop-ethyl and quizalofop-acid were more toxic than (R)-enantiomers. The toxicity of the metabolite to earthworm was much higher than the parent compound.